(untitled) (Gaceta de Ciencias Veterinarias, 2018)
This work contains the initial outcomes from studies conducted to analyze thyroid toxicity associated with potassium iodide overdose. This project is based in the histopathological finding of Hürthle cells in a thyroid gland obtained from a rabbit housed in an animal facility. The goal of this study is to report thyroid toxicity associated with oral administration of iodide through clinical signs, histopathology and ultrasound scan. The iodide was used as potassium iodide (KI) iodide in female New Zealand rabbits (Oryctolagus Cuniculus) at a concentration of 200 ppm (200mg/L) in drinking water administered over a 4-week period. Rabbits treated with KI showed distress, slight lymphopenia and neutropenia. Ultrasound valuation of the thyroid gland revealed multifocal cystic space. Histopathology evaluation showed follicular cells with vacuolar degeneration and parafollicular depletion. Preliminary results of the present study indicate that potassium iodide may disrupt thyroid function by direct cytotoxicity to follicular epithelial cells. Although we have to increase animal numbers, include male rabbits and optimize potassium iodide dose, the toxicological model presented in this work represents an opportunity to study toxicological disorders affecting the thyroid gland.